Insights into midgut cell types and their crucial role in antiviral immunity in the lepidopteran model Bombyx mori - Awais, Mian Muhammad; Fei, Shigang; Xia, Junming; Feng, Min; Sun, Jingchen (Frontiers in Immunology, 2024)
The midgut, a vital component of the digestive system in arthropods, serves as an interface between ingested food and the insect’s physiology, playing a pivotal role in nutrient absorption and immune defense mechanisms. Distinct cell types, including columnar, enteroendocrine, goblet and regenerative cells, comprise the midgut in insects and contribute to its robust immune response. Enterocytes/columnar cells, the primary absorptive cells, facilitate the immune response through enzyme secretions, while regenerative cells play a crucial role in maintaining midgut integrity by continuously replenishing damaged cells and maintaining the continuity of the immune defense. The peritrophic membrane is vital to the insect’s innate immunity, shielding the midgut from pathogens and abrasive food particles. Midgut juice, a mixture of digestive enzymes and antimicrobial factors, further contributes to the insect’s immune defense, helping the insect to combat invading pathogens and regulate the midgut microbial community. The cutting-edge single-cell transcriptomics also unveiled previously unrecognized subpopulations within the insect midgut cells and elucidated the striking similarities between the gastrointestinal tracts of insects and higher mammals. Understanding the intricate interplay between midgut cell types provides valuable insights into insect immunity. This review provides a solid foundation for unraveling the complex roles of the midgut, not only in digestion but also in immunity. Moreover, this review will discuss the novel immune strategies led by the midgut employed by insects to combat invading pathogens, ultimately contributing to the broader understanding of insect physiology and defense mechanisms.